The utility of anatomy assessment in preclinical undergraduate medical curriculum: a scoping review protocol - Alias, Aspalilah; Abas, Razif; Choy, Ker Woon; Wong, Kah Hui; Hadie, Siti Nurma Hanim (Penerbit Universiti Sains Malaysia, 2024)
Anatomy has been taught predominantly in the preclinical years. However, little guidance exists for medical educators in designing appropriate assessments of anatomy knowledge. In general, medical schools implement and determine their own curricula and methods of assessment. The purpose of this scoping review is to examine the breadth of literature regarding the utility of anatomy assessments, which will be reported whether they have been investigated in terms of validity, reliability, practicality, feasibility, cost-effectiveness, and educational impact in the included resources. This scoping review will be conducted using the Joanna Briggs Institute (JBI) scoping review guideline, and its protocol is outlined to systematically map the utility of anatomy assessments in preclinical undergraduate medical curricula over the past 20 years. Primary data will be searched from relevant studies, review articles, and grey literature sources between 2002 and 2023. The resource searching will be performed using the three-step search strategy, namely review search, study selection, and evidence charting, which will involve four electronic databases and two independent reviewers. As secondary research, this review does not require ethical approval. The review will not only permit better comparisons of anatomy assessment and foster meaningful evaluation of both medical students and teaching establishments to take place in the anticipation of ensuring the constructive alignment in anatomy education but also produce important information on the quality of anatomy assessment in the context of the undergraduate medical curriculum. The findings will be disseminated through journals and conferences targeting anatomy educators worldwide.